Obeying the truth Paul's ethics in Galatians - Barclay, John M.G. (Minneapolis, MN Fortress, 1988)
Includes bibliographical references and indexes.
First published: T. and T. Clark, c1988 in series : Studies of the New Testament and its world.
Keywords: Bible. N.T. Galatians -- criticism, interpretation, etc; Ethics in the Bible